2022
DOI: 10.1155/2022/1681038
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Radical Laparoscopic Surgery and Conventional Open Surgery on Surgical Outcomes, Complications, and Prognosis in Elderly Patients with Bladder Cancer

Abstract: Background. Bladder cancer is a common malignant tumor of the urinary system in the clinic. It has multiple lesions, easy recurrence, easy metastasis, poor prognosis, and high mortality. Objective. The aim of this study is to investigate the impact of laparoscopic radical cystectomy (LRC) and open radical cystectomy (ORC) on the surgical outcome, complications, and prognosis of elderly patients with bladder cancer. Materials and Methods. One hundred elderly bladder cancer patients who underwent surgery in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…One of the most frequent malignant tumors of the urinary system, bladder cancer accounts for roughly 3.0 percent of new cases and 2.1 percent of cancer-related fatalities [ 1 ]. High incidence rate, prevalence, recurrence, and mortality of bladder cancer indicate that it is still an unsolved clinical and social problem [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent malignant tumors of the urinary system, bladder cancer accounts for roughly 3.0 percent of new cases and 2.1 percent of cancer-related fatalities [ 1 ]. High incidence rate, prevalence, recurrence, and mortality of bladder cancer indicate that it is still an unsolved clinical and social problem [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The major types of complications were urinary tract infection and intestinal obstruction, followed by colitis, sepsis, and acute renal failure 5,16 . LRC, MIES‐ RC, and RARC also had several complications at a constant rate 6,17–19 . Interestingly, in the current Japanese nationwide database study, the incidence of complications after RC was shown to be significantly lower in the MIS group than in the ORC group.…”
Section: Discussionmentioning
confidence: 92%
“…Regardless of the method of laparoscopic or conventional open surgery, these incisions are prone to numerous complications bearing potential to impede patient's recuperation and increase the likelihood of adverse health outcomes. Illnesses, dehiscence and delayed healing are not trivial annoyances; rather, they are significant challenges that can extend patients' hospital stays, escalate healthcare expenditures and negatively impact their health 5,6 . These patients are more susceptible to complications due to both intrinsic and extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Illnesses, dehiscence and delayed healing are not trivial annoyances; rather, they are significant challenges that can extend patients' hospital stays, escalate healthcare expenditures and negatively impact their health. 5,6 These patients are more susceptible to complications due to both intrinsic and extrinsic factors. Intrinsic factors include nutritional status, age and comorbidities.…”
Section: Introductionmentioning
confidence: 99%